1991
DOI: 10.1046/j.1468-2982.1991.1102097.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood Magnesium Levels in Migraine

Abstract: Serum and erythrocyte magnesium levels were screened between attacks in patients with migraine without aura (n = 38) and with aura (n = 6), and for comparison in a group of patients suffering from chronic tension-type headache (n = 25) as well as a group of neurological, non-headache patients (n = 19). Serum magnesium levels were not significantly different between the four groups of patients. In contrast, magnesium in erythrocytes was on average significantly reduced in patients with migraine without aura com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 3 publications
1
45
2
Order By: Relevance
“…Migraine has been linked to low levels of magnesium in serum and cerebrospinal fluid (CSF) (414,457). Migraine headaches are the consequence of cortical spreading depression (CSD), which consists of an intense membrane depolarization and repolarization in neurons and glial cells (308,388).…”
Section: Migrainementioning
confidence: 99%
“…Migraine has been linked to low levels of magnesium in serum and cerebrospinal fluid (CSF) (414,457). Migraine headaches are the consequence of cortical spreading depression (CSD), which consists of an intense membrane depolarization and repolarization in neurons and glial cells (308,388).…”
Section: Migrainementioning
confidence: 99%
“…Electrophysiological studies using TMS indicate contradictory results [for review, see (11)(12)(13)]. However, several lines of evidence regarding biochemical data (14)(15)(16), familial hemiplegic migraine (FHM) (17) as well as cortical spreading depression (CSD), which is responsible for the aura symptoms in migraine (18,19), support the hypothesis of cortical hyperexcitability in migraine. Clarke et al (20) have demonstrated a reduction of pain intensity by TMS administered immediately after the onset of migraine headaches.…”
Section: Introductionmentioning
confidence: 99%
“…In 1976, Durlach [1] found increased concentration of magnesium in the urine of migraine patients and presumed it to be a result of a transitory serum magnesium decrease in migraine attack. This hypothesis was further corroborated by the observations that in migraine patients intracellular magnesium was reduced during attacks in the brain [2], serum [3,4] and saliva [4], and between attacks in blood [5], erythrocytes, mononuclear cells [6,7] and cerebrospinal fluid [8]. However, several studies did not confirm these findings [9,10].…”
Section: Introductionmentioning
confidence: 79%